PENGARUH STRUKTUR MODAL DAN KEBIJAKAN DIVIDEN TERHADAP NILAI PERUSAHAAN PADA PT BANK NEGARA INDONESIA (PERSERO) TBK PERIODE 2014-2024 - Layali, Nurul; Noryani, Noryani (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2025)
. This study aims to examine the effect of Capital Structure and Dividend Policy on Firm Value at PT Bank Negara Indonesia (Persero) Tbk. for the period 2014–2024. The research employs a quantitative associative approach, analyzing the relationship between independent and dependent variables. Data analysis techniques include descriptive statistics, classical assumption tests, multiple linear regression, t-test, F-test, and the coefficient of determination (R²) with the assistance of SPSS version 26 software. The partial test results show that capital structure has no significant effect on firm value (tcount 0,028 < ttable 2,30600; significance 0,978 > 0,05), and similarly, dividend policy also has no significant effect on firm value (tcount 1,357 < ttable 2,30600; significance 0,212 > 0,05). Simultaneously, capital structure and dividend policy do not have a significant effect on firm value (fcount 1,264 < ftable 4,459; significance 0,333 > 0.05). The coefficient of determination (R²) is 5%, indicating that capital structure and dividend policy explain only a small portion of the variation in firm value, while the remaining 95% is influenced by other factors outside this study.